Perbandingan efektivitas seduhan jahe merah (zingerber officiale var rubrum rhizoma) dengan air kelapa hijau (cocos nucifera linn var viridis) terhadap penurunan skala nyeri haid (dismenore) pada siswi - Cut Oktaviyana; Khaira Rizki; Balqis Adilla (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Dysmenorrhea is a frequent complaint experienced by female students that causes discomfort to the sufferer and also, they do not know how to reduce menstrual pain. Purpose: To determine the comparison of the effectiveness of red ginger (Zingerber officiale var rubrum rhizoma) with green coconut water (Cocos nucifera linn var viridis) on reducing the scale of menstrual pain (dysmenorrhea) in female students of SMA Negeri 1 Montasik. Method: Quantitative research with a quasy experimental design through a two-group pre-test and posstest design approach consisting of 2 groups, each of which is given a different intervention. Using observation sheets and NRS (Numeric Rating Scale) scales with a sample of 30 respondents. This research was conducted at SMA Negeri 1 Montasik starting on May 22-June 29. Results: The study showed that the mean rank of green coconut water was 43.08 while the mean rank of red ginger brew was 17.92. The results of the mann whitney test obtained a P value of 0.001 <0.05 which means that there is a comparison of the effectiveness of giving red ginger (Zingerber officiale var rubrum rhizoma) to reduce the scale of menstrual pain (dysmenorrhea) in female students. Conclusion: There are differences in the administration of green coconut water and red ginger steeping on reducing menstrual pain in female students at SMA Negeri 1 Montasik, where red ginger water is more effective in reducing dysmenorrhea pain than green coconut water. Suggestion: Non-pharmacological interventions such as red ginger water and green coconut water are recommended.